2021
DOI: 10.1016/j.reth.2021.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Immune evasion by cancer stem cells

Abstract: Tumor immunity represents a new avenue for cancer therapy. Immune checkpoint inhibitors have successfully improved outcomes in several tumor types. In addition, currently, immune cell-based therapy is also attracting significant attention. However, the clinical efficacy of these treatments requires further improvement. The mechanisms through which cancer cells escape the immune response must be identified and clarified. Cancer stem cells (CSCs) play a central role in multiple aspects of malignant tumors. CSCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 201 publications
(195 reference statements)
2
61
0
Order By: Relevance
“…Miao et al (2019) demonstrated that TGF-β-enriched CSCs dampened the cytotoxicity of adoptive T cells by promoting the exhaustion state through CD80-CTLA4 interaction in squamous cell carcinoma. The findings of adaptive immune resistance raised from CSCs against immunotherapy echoes with the previously proposed immunosuppressing feature of CSC, and furthermore emphases CSC as the root of tumor relapse (Tsuchiya and Shiota, 2021).…”
Section: Development Of Csc-targeted Immunotherapysupporting
confidence: 68%
See 2 more Smart Citations
“…Miao et al (2019) demonstrated that TGF-β-enriched CSCs dampened the cytotoxicity of adoptive T cells by promoting the exhaustion state through CD80-CTLA4 interaction in squamous cell carcinoma. The findings of adaptive immune resistance raised from CSCs against immunotherapy echoes with the previously proposed immunosuppressing feature of CSC, and furthermore emphases CSC as the root of tumor relapse (Tsuchiya and Shiota, 2021).…”
Section: Development Of Csc-targeted Immunotherapysupporting
confidence: 68%
“…However, the preferential tumorigenic capability of CSCs in NOD/SCID mice suggests that there are underlying immunosuppressive mechanisms for CSCs to dodge from NK cell specific killing ( Al-Hajj et al, 2003 ; Tsuchiya and Shiota, 2021 ). It has been reported that CSCs escape NK-mediated cytotoxicity via various mechanisms by tuning NK receptors.…”
Section: Natural Killer Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent evidence shows that CSCs harbor the capacity of immuno-suppression via several mechanisms; it was revealed that some well-known immunosuppressive molecules, such as PD-L1 and CTLA-4, were higher expressed in CSCs than in common tumor cells [ 174 , 175 ]. Antigen presentation plays a crucial role in cells immunity, it was indicated that CSCs could impair the antigen presentation by downregulating the expression of MHC molecules and some antigen processing molecules, such as transporter associated with antigen processing (TAP) and β-macroglobulin [ 176 ]; researchers also found that the abnormal expression of tumor-associated antigens in CSCs contributed to immune invasion via reducing immunogenicity; CSCs could also promote to build suppressive TME via recruiting some immune cells, such as tumor-associated macrophage (TAM) and regulatory T cell(Treg), and secreting some immuno-suppressive molecules, such as CD200, TGF-βand IFNs, to inhibit CSCs-targeted immune-response [ 177 ], Hiroyuki Tsuchiya et al also summarized that CSCs could impair NK cell function, such as inhibiting the release of cytolytic granules, regulating the expression of the different NK-cell ligands, to escape immune response, they thought the characteristic of immune invasion was a more fundamental feature to CSCs than the tumor-initiating property [ 178 ]. It is necessary to find some new strategies to target CSCs via immunity methods.…”
Section: Targeted Strategies Of Cscsmentioning
confidence: 99%
“…However, the genetic and cellular heterogeneity of the surrounding tumor microenvironment (TME) complicated the clinical efficacy of those treatments, which requires further understanding of the multiple aspects of tumor biology [ 4 ]. Along with the genetic and epigenetic instabilities, the nongenetic intra-tumor heterogeneity and plasticity conduct therapy failure due to the presence of the rare population of cancerous cells known as cancer stem cells (CSCs) or cancer-initiating cells (CICs) [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%